O trabalho da mulher nos agroecossistemas um estudo no projeto de assentamento Dandara Malhador (SE) - Amado, Maria Zélia Alves (2007)
At the last decade, the growth and actuation of brazilian woman in the work market has been extremely positive. In private, the performance of agricultural woman in the productive process of agriculture, assuring through the developed activities, contribution to the alimentary security. The research had for objective to describe the woman work in the agro ecosystems, aiming at subsidizing the planning of the institutions that act with woman in the context of familiar agriculture. It was developed a case study at the settlement project Dandara, Malhador municipality SE. The research was carried through bibliographical revision, collects of secondary data and application of a half-structuralized questionnaire. It was verified that woman has essential everyday life participation of agricultural activities, contributing of decisive way in the family foods production and the consumer market, but her introduction in the participation process and qualification technique don t have favored their organizations and they don t have decision power. The actions of the public politics elaborated by the government in the perspective of the equality promotion between men and women and sustainable development in the practical still leaves many gaps in advance terms in the implementation and indicate the challenge that still have to overcome. The necessity of bigger participation and knowledge is observed in the woman in such a way to favor the inclusion of analysis of this reality and methods can be searched to problem solution under perspective of transformation support, in the cultural social, economic and environmental dimension.